D2-Like Receptors Mediate Dopamine-Inhibited Insulin Secretion via Ion Channels in Rat Pancreatic β-Cells - Liu, Mengmeng; Ren, Lele; Zhong, Xiangqin; Ding, Yaqin; Liu, Tao; Liu, Zhihong; Yang, Xiaohua; Cui, Lijuan; Yang, Lijun; Fan, Yanying; Liu, Yunfeng; Zhang, Yi (Frontiers in Endocrinology, 2020)
Dopamine (DA) has a vital role in the central nervous system, and also modulates lipid and glucose metabolism. The present study aimed to investigate the effect of dopamine on insulin secretion and the underlying mechanisms in rat pancreatic β-cells. Data from the radioimmunoassay indicated that dopamine inhibited insulin secretion in a glucose- and dose-dependent manner. This inhibitory effect of dopamine was mediated mainly by D2-like receptor, but not D1-like receptor. Whole-cell patch-clamp recordings showed that dopamine remarkably decreased voltage-dependent Ca2+ channel currents, which could be reversed by inhibition of the D2-like receptor. Dopamine increased voltage-dependent potassium (KV) channel currents and shortened action potential duration, which was antagonized by inhibition of D2-like receptors. Further experiments showed that D2-like receptor activation by quinpirole increased KV channel currents. In addition, using calcium imaging techniques, we found that dopamine reduced intracellular Ca2+ concentration, which was also reversed by D2-like receptor antagonist. Similarly, quinpirole was found to decrease intracellular Ca2+ levels either. Taken together, these findings demonstrate that dopamine inhibits insulin secretion mainly by acting on D2-like receptor, inhibiting Ca2+ channels and activating Kv channels. This process, in turn, results in shortened action potential duration and decreased intracellular Ca2+ levels in β-cells. This work thus offers new insights into a glucose-dependent mechanism whereby dopamine regulates insulin secretion.